Hyponatremia review - Castellanos, Laura (2016)
Hyponatremia is the most common electrolyte imbalance in clinical practice; it is also the most under-diagnosed. Morbidity and mortality are significantly increased in patients with symptomatic hyponatremia in contrast to patients whose sodium concentration is normal. This article offers a review addressing epidemiology, diagnosis and therapeutic approach of hyponatremia.